HOSPITALITY ENGLISH FOR SPA THERAPISTS IN BANYAN TREE HOTELS AND RESORTS - Nugraheni, Ratnasari (LLT Journal: A Journal on Language and Language Teaching, 2018)
This study is a preliminary study of research and design for hospitality English for SPA therapist in Banyan Tree Hotels and Resorts at Bintan Island. The purpose of this study is to help the English teacher to provide a successful English training since a good English proficiency used in the hospitality industry is obliged, especially for an-international-five-star-hotel-brand. The nature of the study is qualitative using RD approach. Since this is only a preliminary study, need analysis becomes the primary focus. The data were collected through interview and observation. The participants were people who are working in SPA department in Banyan Tree Bintan, such as SPA trainer, SPA therapist, and SPA manager.